2021
DOI: 10.3390/ijerph18063262
|View full text |Cite
|
Sign up to set email alerts
|

Development and Effectiveness of a Patient Safety Education Program for Inpatients

Abstract: Background: Patient safety is considered an important issue in the field of healthcare, and most advanced countries. Purpose: This study was designed to evaluate a patient safety education program among hospitalized patients. Of the 69 participants, 33 completed the patient safety education program while the 36 remaining participants were given educational booklets. The program was used to measure knowledge about patient safety, patient safety perception, and willingness to participate in patient safety. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
10

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 47 publications
0
14
0
10
Order By: Relevance
“…Twelve studies (100%) of experimental design were included, of which five (41.7%) were randomized clinical trials (20)(21)(22)(23)(24) and seven (58.3%) were quasi-experimental studies (25)(26)(27)(28)(29)(30)(31) . The articles included were produced in the United States of America (21,27,28) , United Kingdom (23,25,26) , Australia (20,30) , South Korea (29,31) , Switzerland (24) and China (22) . The sample variability ranged from 65 to 2115 individuals and the language adopted by all studies was English (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Twelve studies (100%) of experimental design were included, of which five (41.7%) were randomized clinical trials (20)(21)(22)(23)(24) and seven (58.3%) were quasi-experimental studies (25)(26)(27)(28)(29)(30)(31) . The articles included were produced in the United States of America (21,27,28) , United Kingdom (23,25,26) , Australia (20,30) , South Korea (29,31) , Switzerland (24) and China (22) . The sample variability ranged from 65 to 2115 individuals and the language adopted by all studies was English (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) .…”
Section: Resultsmentioning
confidence: 99%
“…The articles included were produced in the United States of America (21,27,28) , United Kingdom (23,25,26) , Australia (20,30) , South Korea (29,31) , Switzerland (24) and China (22) . The sample variability ranged from 65 to 2115 individuals and the language adopted by all studies was English (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) . The educational interventions used were verbal guidance or written material (21,23,24,28) (33,3%), technological resources (videos, e-books, electronic applications) (22,25,27,29,31) (41.7%) or both (20,26,30)…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study found that nurses in tertiary hospitals have self-reported high levels of awareness and intention to report adverse events, which is better than previously reported by Chegini et al 35 and Chiang et al 36 Many countries have tried to implement patient safety education programs and ensure the quality of patient care. 37 , 38 Similarly, the Chinese National Health Commission 39 also emphasized the importance of adverse event reporting and issued a series of policies on how to improve the adverse event reporting system and encourage nurses to actively report adverse events. Besides, tertiary hospitals have made considerable efforts in medical quality and patient safety issues, such as simplifying the reporting process of adverse events, initiating non-penalties and rewards, and strengthening training on the adverse event reporting process and reporting system.…”
Section: Discussionmentioning
confidence: 99%